Remote Predictive Mapping 1. Remote Predictive Mapping (RPM): A Strategy for Geological Mapping of Canada’s North - Schetselaar, E.M.; Harris, J.R.; Lynds, T.; de Kemp, E.A. (Geoscience Canada, 2007)
SUMMARY Remote Predictive Mapping (RPM) techniques are being developed and refined by the Geological Survey of Canada for mapping Canada’s North. Remote Predictive Mapping should be considered an integral part of the geological mapping process designed to involve compilation, and re-compilation of data derived from existing geological maps, aerial photographs, satellite imagery, and airborne geophysical data. Predictive geological maps may be iteratively revised and upgraded to publishable geological maps by integrating remotely sensed data with newly acquired field and laboratory data, as RPM techniques are progressively tested and insight evolves. A predictive map, produced without collection of new, field-based data, may also serve as a first-order geologic map in areas where field-based studies cannot be accomplished due to expense of field access or remoteness. As a welcome consequence of adopting RPM into the normal work flow of any mapping or exploration project, there will, by necessity, be greater participation and integration of expertise of field geologists, geophysicists, Geographic Information System (GIS) and remote sensing specialists. Significantly, RPM also encourages geoscience organizations to make full use of all available geoscience data. This paper outlines a strategy for RPM and provides processing and interpretation examples based on a variety of geoscience data and interpretation techniques to be employed for geologic mapping.